Fatal pesticide intoxication - case report of a 2 patients - Tkaczyk, Jędrzej; Brożyna, Klaudia; Ciechański, Krystian; Radzka, Agnieszka; Tchórz, Michał (Journal of Education, Health and Sport, 2018)
Pesticides is a collective term for a group of chemicals used predominantly in agriculture and against vectors in vectorborne diseases such as malaria, filariasis, etc. Organophosphates (OP) have become nowadays the most widely used pesticides among the world. However, they are very highly toxic to humans. Poisoning with OP is a life - threatening condition. It is responsible for the symptoms due to a cholinergic effects. The Acetylcholinesterase (ACHE) enzyme inhibition leads to an acetylcholine accumulation, which causes symptoms such as diarrhea, sweating, vomiting, small pupils, muscle tremors, increased saliva and tears production and confusion. Other type of pesticides are also common used in agriculture. Glyphosate is a broad‐spectrum systemic herbicide used to kill weeds. It is promoted by the manufacturer as having no risks to human health.We present two patients with a fatal pesticide poisoning. First patient drank OP agent, which was decanted in a non-original bottle. Despite the intensive treatment, including high doses of atropine, and toxogonine, patient died after 6 days due to acute respiratory failure. The second one, tried to commit suicide by drinking 2 glasses of a pesticide called ‘Roundap’ (glyphosate). Short time after admission to a hospital, a myocardial infarction occurred. The patient died the same day, due to a cardiac arrest.